Hybrid OCDMA/WDM system using complementary detection technique for FTTH access networks - Nasim, Ahmed; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Hilal Adnan, Fadhil, Dr.; R. Badlishah, Ahmad, Assoc. Prof. Dr.; Mohd Abdur, Rashid, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/